The Viterinary Profession in Greece: Review of the present and prospects for the future. IV Anticipated developments for veterinary science. A. Expectations of the profession - ΧΑΤΖΗΟΛΟΣ, ΒΑΣΙΛΕΙΟΣ Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
No abstract (available).